2007
DOI: 10.1177/154405910708600708
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Force Induces High RANKL Expression in Human Periodontal Ligament Cells

Abstract: Intermittent compressive force stimulates bone resorption in orthodontic treatment. This study examined the molecular mechanism in human periodontal ligament (PDL) cells stimulated by an intermittent force. PDL cells were subjected to compressive force (2.0 or 5.0 g/cm(2)) for 2-4 days. Continuous or intermittent force was applied all day or for 8 hrs per day, respectively. At days 3 and 4, cell damage was less with intermittent force than with continuous force. At day 4, RANKL and IL-1beta expressions were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 28 publications
1
59
2
1
Order By: Relevance
“…Compressive force significantly increases the expression of RANKL but decreases osteoprotegerin, a decoy receptor for RANKL, in human PDL fibroblasts (PDLFs) cultured in vitro in a time-and magnitude-dependent manner (Nishijima et al, 2006). It has also been demonstrated that intermittent force up-regulates RANKL expression via IL-1 in human PDLFs (Nakao et al, 2007). The results from these studies suggest that enhanced osteoclastogenesis in compression side PDLs may be partly caused by compressive force-induced RANKL expression in PDLFs.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Compressive force significantly increases the expression of RANKL but decreases osteoprotegerin, a decoy receptor for RANKL, in human PDL fibroblasts (PDLFs) cultured in vitro in a time-and magnitude-dependent manner (Nishijima et al, 2006). It has also been demonstrated that intermittent force up-regulates RANKL expression via IL-1 in human PDLFs (Nakao et al, 2007). The results from these studies suggest that enhanced osteoclastogenesis in compression side PDLs may be partly caused by compressive force-induced RANKL expression in PDLFs.…”
Section: Introductionsupporting
confidence: 48%
“…Subsequently, osteoclast differentiation may be induced by the additive actions of RANKL and VEGF. In addition to hypoxia, compressive force also up-regulates RANKL expression in PDLFs (Kanzaki et al, 2002;Nakao et al, 2007), suggesting that in compression side PDLs, RANKL expression is strongly induced by both compressive force and local hypoxia. Given that hypoxia-induced HIF-1α down-regulates osteoprotegerin expression in chondrocytes (Shirakura et al, 2010), the ratio of RANKL to osteoprotegerin may be increased in compression side PDLs, creating favorable conditions for osteoclastogenesis.…”
Section: A B Cmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26] Among the manner of mechanical stress, compressive stress was used to confirm the role of PDL cell in the tissue remodeling process of the compressive side during orthodontic tooth movement with particular focus on osteoclastogenesis. Hydrostatic compression, 22,23 reverse-tension compression, 24 and direct contact compression methods 19,25,26 were used to provide compressive stress on cultured cells. The direct contact compression method appeared to mimic most in vivo systems in orthodontic treatment because a static compressive force is applied to the tooth in daily orthodontic practice and that PDL tissue is compressed directly between two hard structures, bone and cementum.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokines are produced by cells in the periodontal tissue as fibroblasts and osteoblasts, and they participate in normal physiological bone turnover and remodeling [11][12][13][14][15][16][17]. Many characteristics of these cytokines are of interest in orthodontics, since cytokines in the GCF reflect the microenvironment of periodontal tissues, in which orthodontic forces are applied [2,4,15]. Several studies also revealed that cytokines are fundamental in cell signaling in bone [14,18,19] and in mediating mechanically induced bone remodeling (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The actions of cytokines include several effects on immune cells and modulation of inflammatory responses [10,11]. The cytokines are produced by cells in the periodontal tissue as fibroblasts and osteoblasts, and they participate in normal physiological bone turnover and remodeling [11][12][13][14][15][16][17]. Many characteristics of these cytokines are of interest in orthodontics, since cytokines in the GCF reflect the microenvironment of periodontal tissues, in which orthodontic forces are applied [2,4,15].…”
Section: Introductionmentioning
confidence: 99%